A SYNCHRONIZED BRAKING SYSTEM - RAJU, Karnam Venkata Manga; MOHAN, Shanmugam (2020)
The present subject matter relates to a synchronized braking system (200). An independent brake actuation lever (210) is coupled to at least one front wheel brake (130) for actuation thereof. A synchronous brake actuation pedal (205) capable of receiving brake actuating forces is pivotably supported to a frame member (105) of the vehicle (100) by a pivot shaft (307). A reaction relay member (310) pivoted about said pivot shaft (307) is capable of rotating independent of the synchronous brake actuation pedal (205). The reaction relay member (310) is communicated to a rear brake actuating member (235) for actuating the rear brake actuating member through reaction of an outer sheath (222) of an intermediate brake cable (220) acting on the reaction relay member (310) during application of the synchronous brake actuation pedal (205). It offers a reliable braking system with reduced joints and is capable of offering superior brake feel. L'invention concerne un système de freinage synchronisé (200). Un levier d'actionnement de frein indépendant (210) est couplé à au moins un frein de roue avant (130) pour l'actionnement de celui-ci. Une pédale d'actionnement de frein synchrone (205) apte à recevoir des forces d'actionnement de frein est supportée de manière pivotante sur un élément de cadre (105) du véhicule (100) par un arbre de pivot (307). Un élément de relais de réaction (310) pivotant autour dudit arbre de pivot (307) est apte à tourner indépendamment de la pédale d'actionnement de frein synchrone (205). L'élément de relais de réaction (310) est en communication avec un élément d'actionnement de frein arrière (235) pour actionner l'élément d'actionnement de frein arrière par la réaction d'une gaine extérieure (222) d'un câble de frein intermédiaire (220) agissant sur l'élément de relais de réaction (310) pendant l'application de la pédale d'actionnement de frein synchrone (205). Il offre un système de freinage fiable avec des raccords réduits et peut offrir une meilleure sensation de freinage.